A comprehensive mechanism of biological and health effects of anthropogenic extremely low frequency and wireless communication electromagnetic fields - Panagopoulos, Dimitris J.; Yakymenko, Igor; Iuliis, Geoffry N. De; Chrousos, George P. (My University, 2025)
Exposure to anthropogenic electromagnetic fields (EMFs), especially those of wireless communications (WC) has increased tremendously. This is an unprecedented phenomenon throughout biological evolution because, all anthropogenic EMFs, being fully polarized, coherent, and, especially WC EMFs, highly variable, differ substantially from the natural EMFs. WC EMFs consist of Microwave (MW) carrier waves, modulated, by Extremely Low Frequency (ELF) signals, and included in on/off pulses repeated at various ELF rates. Moreover, they exhibit intense random variability, mainly in the Ultra Low Frequency (ULF) band. Thus, WC EMFs are a combination of MW and ELF/ULF EMFs. The combination of polarization/coherence and intense low-frequency (ELF/ULF) variability seems to be the key to EMF-bioactivity. Epidemiological and laboratory studies highlight a connection between ELF or WC EMF exposure and cancer, infertility, electro-hypersensitivity, and various other pathologies. Studies also find DNA damage and Oxidative Stress (OS) which explain these pathologies. While man-made EMFs cannot directly ionize molecules, they are capable of doing this indirectly in biological tissue, by triggering the biosynthesis of Reactive Oxygen Species (ROS) which can damage biomolecules, including DNA. The (over)production of ROS and the consequent OS are triggered by irregular gating of Voltage-Gated Ion Channels (VGICs) in the cell membranes as described by the Ion Forced Oscillation (IFO)-VGIC mechanism: Mobile ions within VGICs forced to oscillate by the applied ELF/ULF EMFs exert forces on the voltage sensors of the VGICs, similar to or greater than the forces that physiologically gate those channels, resulting in their irregular gating (dysfunction). Dysfunction of ion channels disrupts intracellular ionic concentrations. This triggers ROS overproduction and OS by the ROS-generating systems/enzymes in the cells, such as the electron transport chain (ETC) in the mitochondria, or the NADPH/NADH oxidases (NOXs), the Nitric Oxide synthases (NOS), etc. The IFO-VGIC mechanism and the consequent OS constitute a comprehensive mechanism that explains all known adverse biological and health effects reported to be induced by anthropogenic EMFs. Вплив антропогенних електромагнітних полів (ЕМП), особливо бездротового зв'язку (БЗ), надзвичайно зріс. Це безпрецедентне явище протягом біологічної еволюції, оскільки всі антропогенні ЕМП, будучи повністю поляризованими, когерентними та, особливо ЕМП БЗ, дуже мінливими, суттєво відрізняються від природних ЕМП. ЕМП БЗ складаються з мікрохвильових (НВЧ) хвиль-носіїв, модульованих сигналами надзвичайно низької частоти (ННЧ) та включених до складу імпульсів вмикання/вимикання, що повторюються з різною частотою ННЧ. Крім того, вони демонструють інтенсивну випадкову мінливість, головним чином у діапазоні наднизьких частот (УНЧ). Таким чином, ЕМП БЗ є комбінацією НВЧ та ЕМП ННЧ/УНЧ. Поєднання поляризації/когерентності та інтенсивної низькочастотної (ННЧ/УНЧ) мінливості, здається, є ключем до біоактивності ЕМП. Епідеміологічні та лабораторні дослідження підкреслюють зв'язок між впливом ЕМП ННЧ або БЗ та раком, безпліддям, електрогіперчутливістю та різними іншими патологіями. Дослідження також виявляють пошкодження ДНК та оксидативний стрес (ОС), які пояснюють ці патології. Хоча штучні електромагнітні поля (ЕМП) не можуть безпосередньо іонізувати молекули, вони здатні робити це опосередковано в біологічних тканинах, запускаючи біосинтез активних форм кисню (АФК), які можуть пошкоджувати біомолекули, включаючи ДНК. (Надмірне) виробництво АФК та подальший ОС запускаються нерегулярним закриттям напругово-залежних іонних каналів (НВК) у клітинних мембранах, як описано в механізмі іонно-вимушених коливань (ІВВ): рухомі іони в НВК, змушені коливатися застосованими ЕМП ELF/ULF, чинять сили на датчики напруги НВК, подібні або більші, ніж сили, які фізіологічно закривають ці канали, що призводить до їх нерегулярного закриття (дисфункції). Дисфункція іонних каналів порушує внутрішньоклітинні концентрації іонів. Це провокує надмірне вироблення активних форм кисню (АФК) та осаду (ОС) системами/ферментами, що генерують АФК, у клітинах, такими як ланцюг транспорту електронів (ЕТЦ) у мітохондріях або НАДФН/НАДН оксидази (НОХ), синтази оксиду азоту (НОС) тощо. Механізм IFO-VGIC та пов'язаний з ним ОС являють собою комплексний механізм, який пояснює всі відомі несприятливі біологічні та оздоровчі наслідки, які, як повідомляється, викликаються антропогенними електромагнітними полями.
Keywords: кафедра екології та екоменеджменту; DNA; electromagnetic field; IFO-VGIC; ion forced oscillation; oxidative stress; ROS; voltage-gated ion channels; ДНК; електромагнітне поле; іонно-вимушені коливання; оксидативний стрес; активні форми кисню; бездротовий зв'язок